(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Cervical cancer is a disease of significant worldwide morbidity and mortality. More than 85% of the disease occurs in developing countries. Bangladesh, like other developing countries faces a burden of the disease. ObJective: To find out the different way of presentation of invasive cervical cancer patients. Methods: This cross-sectional study was carried out in the Gynaecologic Oncology wing of the Department of Obstetrics and Gynaecology of Bangabandhu Sheikh Mujib Medical University (BSMMU) during 1st January 2007 to 30th April 2008. One hundred and four patients with invasive cervical cancer admitted in hospital were enrolled in the study by purposive sampling. All the information were collected in a pre-designed structured questionnaire. Data were analyzed using statistical program SPSS version: 17.0. Frequency distributions were used to present the characteristics of the patients. Chi-square test was calculated and the significant level was set at P<0.05. Results: Maximum patients (60.6%) were in stage II. Majority of the patients (61.5%) presented with abnormal bleeding. Exophytic growth was found in the majority of the patients (71.2%). Squamous cell carcinoma was more (92.3%) in the majority of patients and adenocarcinoma was more in younger age group. Conclusion: The status of the patients irJ this study reflects advanced stage of the disease at presentation and the peak incidence was observed in 36-45 years age group.